The Impact of the soap opera Bond of Love on the behavior of the people of Plered Purwakarta - Fitri Sukayawati; Khaerunnisa Khaerunnisa; Tasya Tasya (Trigin Publisher, 2020)
This study aims to reveal how people's behavior after watching the soap opera Ikatan Cinta and what factors cause changes in people's behavior after watching the soap opera Ikatan Cinta. This study uses a descriptive approach with quantitative research methods. This method provides an illustration of how the influence of soap operas on the behavior of the plered community. The quantitative descriptive research method instrument that the researcher uses is a questionnaire. This study seeks information about the impact of soap operas on people's behavior, as well as how respondents respond to soap operas that are currently booming. The results showed that almost all plered people were exposed to the soap opera Ikatan Cinta.